Pengaruh Metode Pembelajaran Penugasan Dan Pemanfaatan Media Pembelajaran Terhadap Hasil Belajar - Ajeng Nuzulia H; Djoko Santoso; Patni Ninghardjanti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2017)
The research aims to know determine whether there are (1) the effect of assignment learning method on introduction administration office course in the XI graders od Administration Office Skill Competency in SMK Negeri 1 Karanganyar in the school year of 2015/2016 ; (2) the effect of utilization of learning media on introduction administration office course in the XI graders od Administration Office Skill Competency in SMK Negeri 1 Karanganyar in the school year of 2015/2016 ; (3) the effect of assignment learning method and utilization of learning media on introduction administration office course in the XI graders od Administration Office Skill Competency in SMK Negeri 1 Karanganyar in the school year of 2015/2016. This study is a quantitative research with descriptive method. The population of research is all XI graders of Administration Office Skill Competency in SMK Negeri 1 Karanganyar in the school year of 2015/2016 consisting of 71 students. The sample consisted of 59 atudents. The sampling technique used is proportional random sampling. Meanwhile technique of collecting data used is questionnaire and documentation technique. Technique of analyzing data used is statistic test with multiple regression analysis. Considering the result of data analysis, it could be conclud that (1) there was a significant effect of assignment teaching methods on learning outcomes Introduction Administrative subjects in class XI Competency Office Administration in SMK N 1 Karanganyar the school year of 2015/2016, is evident from the correlation value of 0.435> rtabel (0.235) and supported from tcount amounted to 5.273> t table (1.995) with a probability value of 0.000 means that less than 0.05 then Ho is rejected and Ha1 accepted ; (2) there is significant influence utilization of instructional media for learning outcomes Introduction Adminisrasi subjects in class XI Competence Offices Office Administration in SMK N 1 Karanganyar the school year of 2015/2016, is evident from the correlation value of 0.440> rtabel (0.235) and supported on value thitung 5.318> t table (1.995) with a probability value of 0.000 means that less than 0.05 then Ho is rejected and Ha2 accepted ; (3) there is significant influence learning method of assignment and utilization of instructional media on the results of study subjects in the class Introduction to Office Administration Office Administration XI Competency SMK N 1 Karanganyar In the school year of 2015/2016, proved of value Fhitung 25.388> F table (3 , 13) with a significance value of 0.000 at significant level of 0.05, then Ho is rejected and HA3 accepted and supported from the value of the effective contribution of the variable method of learning the assignment and utilization of instructional media contributed 42.7% to the learning outcomes of subjects Introduction to Office Administration.